The Wedding Photographer's Planner. - Kim, Kenny (John Wiley & Sons, 2010)
A full-color reference to planning for and executing a successful wedding day shoot. Wedding photography has become a major industry, and the number of photographers getting into this field is rapidly increasingmaking it even more competitive. Written by top wedding photographer, Kenny Kim, this full-color reference walks you through all the major (and minor) steps involved in planning and organizing a successful wedding day shoot. You'll get unique advice on everything from your initial meeting with the engaged couple to the final presentation of the commemorative book. Packed with checklist.